Intensive Management of New Hampshire and Giriraja Chickens for Generating Premium Cash Income - Neupane, D.; Karki, M.; Shrestha, S. B. (Nepal Journal of Science and Technology, 2015)
Comparative performance of New Hampshire and Giriraja breeds of chicken was studied at Swine and Avian Research Program, Khumaltar. The data on feed intake, weight gain and mortality of the chicks were recorded up to 12 weeks of age. All the experimental birds were reared with commercial broilers feed (Pancha Ratna feed) under similar management. Significant (<0.01) effect of breed on body weight was observed with Giriraja showing superior to New Hampshire. Effect of sex on body weight was also found significant (P<0.01). At twelve-week of age, higher body weight was observed for Giriraja male (2082 g) followed by Giriraja female (1655 g), New Hampshire male (1338 g) and New Hampshire female (1051 g) with cumulative FCR of 3.40,3.78,3.87 and 3.90 respectively. Irrespective of sex, Giriraja exhibited better FCR than New Hampshire at all weeks of rearing. The cumulative mortality was found as 6.21% and 12.25% for New Hampshire and Giriraja respectively. Up to 12 weeks of rearing, higher saving per bird was observed in Giriraja (Rs132.39) than that of New Hampshire (Rs 67.09). The findings of this study revealed that these dual-purpose breeds have potentiality to be competitive meat producers in intensive management. Giriraja is better than New Hampshire in terms of higher growth, better feed efficiency and saving per birds but need for proper health management particularly in the early growth stage. Looking at the havier body weight with having better feed efficiency and higher saving per bird of 12 week rearing, Giriraja could be the choice of economical viable intensive farming for generating premium cash income whereas New Hampshire appears to be suitable for scavenging and semi- scavenging management. DOI: http://dx.doi.org/njst.v15i2.12109 Nepal Journal of Science and Technology Vol. 15, No.2 (2014) 23-28